Frequency of retained third molars in relation to facial biotype. a cross-sectional study - Zeta Rodríguez, Taylor Augusto (2022)
Objective: This study aims to determine the frequency of retained third molars in relation to facial biotype, the data were collected by using the patients’ 2D studies (panoramic and cephalometric) attending the imaging center ZETA-EXMED in the period November 2018 to December 2021, in the city of Lima, Peru. Methods: The type of study used for this research are observational, descriptive, cross-sectional, and retrospective. For the present study, 6000 cases were evaluated, each case consists of one panoramic radiographic image and one cephalometric image, both taken to the patient on the same date, of these, only 150 cases that met the selection criteria were included in this study. Measurements about frequency of retained third molars in relation to facial biotype were done by a trained and calibrated researcher, using NemoCeph software for the cephalometric tracing. The statistical analysis was done using SPSS program version 1.0.0.1401 (SPSS Inc., USA) and the Chi square test (p <0.05). Results: Of the 150 cases observed, 91 were women (60.66%) and 59 were men (39.33%). According to the results, dolichofacial biotype had the highest frequency among males with a total of 27 cases (45.80%), while the brachyfacial biotype was more prevalent among females, with a total of 35 cases (38.50%). In addition, out of the total number of retained third molars evaluated (403 pieces), 141 were present in cases with dolichofacial biotype, followed by the mesofacial biotype with 139 pieces and finally the brachyfacial biotype with 123 pieces. Regarding the evaluation of retained third molars according to their position and facial biotype, 63 retained third molars were found in mesioangulated position and 28 retained third molars in dolichofacial / distoangular position, followed by 48 pieces in the vertical position in brachyfacial. Conclusions: There is not significant association between the quantity of retained third molars and their positions, in relation to facial biotype, although there is a significant association between facial biotype and the patient's sex, so it was concluded that Dolichofacial biotype has the highest frequency in males, while the Brachyfacial biotype is seen more frequently among females.